Assessment of Sail River Water Quality in Pekanbaru City Using the STORET and Pollution Index (IP) Methods - Fitria, Dewi; Suci, Nabila Rahma; Darmayanti, Lita (Jurnal Rekayasa Kimia & Lingkungan, 2025)
The Sail River acts as the main drainage in Pekanbaru City. Several community activities around the Sail River, such as residential areas, plantations, livestock, shops, markets, and schools, cause decreasing in water quality in the Sail River. For this reason, it is necessary to analyze the water quality of the Sail River using the STORET method and the Pollution Index. The physical (temperature, TSS, TDS), chemical (pH, COD, DO, Pb), and biological (total coliform) parameters were analyzed. The results of the water quality analysis obtained were compared with Class II Water Quality Standards based on PP No. 22 of 2021. The results of the analysis of the quality status of the Sail River downstream based on the STORET method over the last five years show a "heavily polluted" condition, while the results of the IP method analysis show a "moderately polluted" condition. Based on the STORET and Pollution Index methods results, sail river needs a pollution control policy and management to overcome the pollution.